Cryo-EM structure of the prohibitin complex in open conformation - Sixing Hong; Zeyuan Guan; Liying Zhang; Jinjin Zhuang; Ling Yan; Yanjun Liu; Zhu Liu; Qiang Wang; Ping Yin (Proceedings of the National Academy of Sciences, 2025)
Prohibitin 1 (PHB1) and Prohibitin 2 (PHB2), two conserved prohibitin members, are primarily localized to the mitochondrial inner membrane (MIM) to form a nanoscale macromolecular prohibitin complex. This prohibitin complex can facilitate the spatial organization of proteins and lipids, thus maintaining cellular metabolism and homeostasis, but its architecture remains largely unknown. Here, we report the cryo-EM structure of a prohibitin complex at 2.8 Å resolution, which contains 11 PHB1–PHB2 heterodimers. This complex displays a bell-like cage, consisting of a lid and a wall, which creates an intermembrane space-facing compartment for the MIM. The lid of the cage is stably assembled, and it is responsible for the prohibitin complex formation. In contrast, the wall of the cage is flexible and exhibits lateral openings, providing a channel for intramembrane exchange of proteins and lipids. These findings provide a structural basis for understanding the scaffold role of the prohibitin complex in organizing intramembrane proteins and lipids.